Pertanggungjawaban Pidana Dalam Kejahatan Yang Melibatkan Artificial Intelligence Dalam Sistem Hukum Pidana Indonesia - Lina Setio Rahayu; Siti Marwiyah; Bachrul Amiq (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The rapid development of Artificial Intelligence (AI) technology has created a new paradigm in the spectrum of crime that challenges the existing criminal law framework. This study examines the concept of criminal liability in crimes involving Artificial Intelligence within the Indonesian criminal law system and explores the harmonization of criminal liability doctrines with the juridical complexities arising from AI technology. This research employs normative legal research using statutory and conceptual approaches by analyzing relevant primary, secondary, and tertiary legal materials. The analysis is grounded in the theories of criminal liability and progressive law. The findings indicate that the Indonesian criminal law system faces significant paradigmatic challenges in constructing criminal liability for AI-related crimes. Traditional criminal liability principles based on the doctrine of geen straf zonder schuld (no punishment without fault) encounter difficulties when applied to AI systems characterized by autonomous learning, autonomous decision-making, and the black-box problem. Therefore, an effective legal response requires a paradigmatic transformation from a positivist-legalistic approach toward a progressive legal framework. Such transformation includes the reconstruction of the concept of mens rea, adaptation of causality theories, and the development of negligence doctrines specifically tailored to AI technologies. Furthermore, the proposed harmonization model should incorporate cascading liability, the principle of meaningful human control, restorative justice, and proportional criminal sanctions while maintaining the fundamental principles of Indonesian criminal law.